Occupational asthma in salbutamol process workers. - Agius, R M (1994)
Occupational asthma after exposure to salbutamol in the pharmaceutical industry has not been previously reported. The occurrence of occupational asthma is described in two pharmaceutical process workers who were likely to have inhaled doses appreciably in excess of the therapeutic dose range. The findings do not lead to an unequivocal conclusion on the mechanism of the asthma but it was probably a pharmacological consequence of high exposure.